Qualitative Assessment of Energy Initiative: Case Study from Liberia - Gul, Ejaz; Chaudhry, Imran Sharif (International Journal of Energy Economics and Policy, 2014)
In policy domain, economics is concerned with decision about the best alternative for undertaking public and private initiatives. Economic decision is a complex issue since many explicit and implicit economic factors affect the available economic alternatives. This is particularly difficult when we have to decide about launching an energy initiative. Generally, economic options are quantitatively evaluated using cost benefit analysis method which considers only explicit factors and does not cater for the opinion of masses about suitability of particular economic option. This shortfall of quantitative assessment is more pronounced in case of energy initiative for which the ultimate recipients are the masses and undertaking of energy initiative has to cater for the consent of the masses. The opinion of people gives important conclusions about explicit and implicit factors affecting the economic options. Thus, for launching an energy initiative, it is more prudent to go for qualitative participatory assessment procedure rather than rigid cost benefit analysis. In 2009, Government of Liberia decided to invest in an energy initiative to generate energy for the diverse consumption. In this case studydiscusses qualitative economic evaluation of three different options considered for the energy initiatives. The study was aimed at finding the relative feasibility of available options based on the opinion of people. For this purpose, instead of using cost benefit analysis method, ItemizedScale survey technique was used to ascertain the economic feasibility of options. Case study contains useful and pertinent policy lessons for implementation. Keywords: Economics; energy; initiative; Itemized Scale; survey JEL Classifications: O22; O55; Q42; Q48.